2014
DOI: 10.1093/mnras/stu897
|View full text |Cite
|
Sign up to set email alerts
|

On the area of accretion curtains from fast aperiodic time variability of the intermediate polar EX Hya

Abstract: We present results of a study of the fast timing variability of the magnetic cataclysmic variable (mCV) EX Hya. It was previously shown that one may expect the rapid flux variability of mCVs to be smeared out at timescales shorter than the cooling time of hot plasma in the post shock region of the accretion curtain near the WD surface. Estimates of the cooling time and the mass accretion rate, thus provide us with a tool to measure the density of the post-shock plasma and the cross-sectional area of the accret… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 73 publications
(83 reference statements)
0
14
0
Order By: Relevance
“…Using the specific accretion rate of a = 3 g cm −2 s −1 and f = 1.6 × 10 −4 , as recently obtained by Semena et al (2014), resulted in both H-and He-like fluxes overestimated by more than an order of magnitude. Fujimoto & Ishida (1997) found that their cooling flow model fit the line ratios of high-Z ions (Z > 14), assuming that the bottom of the accretion column has a temperature kT B = 0.65 keV, preventing any cooling below this temperature.…”
Section: The Isobaric Cooling Flow Derivation Of a Physically-based mentioning
confidence: 73%
See 3 more Smart Citations
“…Using the specific accretion rate of a = 3 g cm −2 s −1 and f = 1.6 × 10 −4 , as recently obtained by Semena et al (2014), resulted in both H-and He-like fluxes overestimated by more than an order of magnitude. Fujimoto & Ishida (1997) found that their cooling flow model fit the line ratios of high-Z ions (Z > 14), assuming that the bottom of the accretion column has a temperature kT B = 0.65 keV, preventing any cooling below this temperature.…”
Section: The Isobaric Cooling Flow Derivation Of a Physically-based mentioning
confidence: 73%
“…If we use M WD = 0.79 M , R WD = 7×10 8 cm, h sh = 0.1 × R WD , and R in = 2.7 × R WD (Revnivtsev et al 2011;Semena et al 2014), we have v ff = 4000 km s −1 . Using the strong shock condition kT shock = 3µm p v 2 ff /16, we find that kT shock ∼ 19 keV.…”
Section: Ex Hyamentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Revnivtsev et al (2011) and Semena et al (2014) modeled the break frequency in the power spectrum of stochastic variability and proposed R in =2.7 R W D . Belle et al (2003), Suleimanov et al (2016) and Echevarria et al (2016) also derived small R in using other methods.…”
Section: Introductionmentioning
confidence: 99%